2010
DOI: 10.1177/1527002510371194
|View full text |Cite
|
Sign up to set email alerts
|

General Ability and Specialization: Evidence From Penalty Kicks in Soccer

Abstract: This article revisits the 2 × 2 penalty kick game and seeks to explain differences in mixed strategies associated with different player types and the relative performance of these player types. The authors show that (a) a kicker’s general ability is a reliable indicator of his success rate, (bi) a kicker’s specialization rate increases with his general ability, and (c) left-footed kickers who present a minority within the total population are characterized by a higher success rate. Consequently, the authors es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 10 publications
1
17
0
2
Order By: Relevance
“…8 When faced with less frequent left-handed opponents, a compromised ability to anticipate shot outcome has been observed in tennis, 7 handball goalkeeping, 9 and volleyball. 4 Similarly in team sports, Baumann et al 10 for example, identified that 76% of left-footed penalties were successful compared to 72% of right-footed in the German Bundesliga between 1995 and 2007. The benefit for left-handers/footers has collectively been termed the negative frequency-dependent advantage hypothesis 8 and suggests performance advantages gained from perceptual-cognitive experience are dependent upon the frequency and similarity of the movements and actions being observed and analysed.…”
Section: Introductionmentioning
confidence: 99%
“…8 When faced with less frequent left-handed opponents, a compromised ability to anticipate shot outcome has been observed in tennis, 7 handball goalkeeping, 9 and volleyball. 4 Similarly in team sports, Baumann et al 10 for example, identified that 76% of left-footed penalties were successful compared to 72% of right-footed in the German Bundesliga between 1995 and 2007. The benefit for left-handers/footers has collectively been termed the negative frequency-dependent advantage hypothesis 8 and suggests performance advantages gained from perceptual-cognitive experience are dependent upon the frequency and similarity of the movements and actions being observed and analysed.…”
Section: Introductionmentioning
confidence: 99%
“…Average player ratings reflect the player's individual performance (Baumann et al, 2011) as well as his contribution to the team performance (Frick, 2010). The ratings are assigned by two sport journalist experts out of a trained, stable expert team from a German Soccer magazine called "Kicker".…”
Section: Operationalization and Measuresmentioning
confidence: 99%
“…As a consequence, there is an extensive literature regarding the aspects of specialization, which in certain occasions can be utilized by various scientific fields and which encapsulates different aspects of the specialization effect, in relation to both financial as well as productivity matters, by proposing respectively various models which embrace or deny specialization. Accordingly, researches that focus on the specializing division of labor inside the marriage (Leahey, 2006;Lee & Ono, 2008); the impact of specialization on productivity ratio, as well as on the employees' burn-out effect (Hsieh & Chao, 2004), but also in the effective-ness is certain sport areas, such as the penalty kicking in soccer (Baumann et al, 2011) constitute typical examples of the multiple functional facets of specialization.…”
Section: Definition and Aspects Of Specializationmentioning
confidence: 99%